צלת א-שקאוף - Buzakhar, Madghis (עיתון קהילת יהודי לוב, 2010)
Keywords: Judaïsme -- Djebel Nefousa

The History Of Nafousa Mountains' Jews - Altaeb, Malak (2020)
Not a single Jew remains in Libya today but their history remains alive. Many of those who once lived home, are scattered all over the world, with stories to tell to their grandchildren. I am sure stories worth telling! Once upon a time, Jews and Muslims lived together in Libya embracing their differences and living in harmony. It is important to know that Jews lived in many parts around Libya, not only in major cities. Indeed, the fact that Libya was an Italian colony and did not fall under the Vichy regime in France made the fate of the Jews of Libya different from that of the Jews of Algeria, Morocco and Tunisia.   I embarked on the journey to find answers about the once who lived home, it is something we cannot simply erase. This dates back to 2016 when I started the process of questioning and though it has only been four years, but I know for fact, I still have a long way to go. However, I managed to get to know Libyan Jews and talk to them and know their families’ stories.   I always try to picture how life was for them in Libya. When I read […]
Keywords: Judaïsme -- Djebel Nefousa

Le destin d’une communauté méditerranéenne. Les mémoires privées des juifs libyens - Lucia Sergio, Marialuisa (EnJeu, 2017)
Keywords: Judaïsme -- Djebel Nefousa

Yefren - Roumani, Maurice (Encyclopedia of Jews in the Islamic World, 2010)
Keywords: Judaïsme -- Djebel Nefousa

Jebel Nafusa - Simon, Rachel (Encyclopedia of Jews in the Islamic World, 2010)
Keywords: Judaïsme -- Djebel Nefousa

Gharian - Roumani, Maurice (Encyclopedia of Jews in the Islamic World, 2010)
Gharian is a town in northwestern Libya about 80 kilometers (50 miles) south of Tripoli in the Nafusa Mountains. It is considered to constitute a single unit with the nearby towns of Tighrinna and Banu Abbas. All three towns had Jewish inhabitants, but most of them lived in Tighrinna, just south of Gharian, which was referred to variously as ḥārat al-yahūd (the Jewish Quarter) and arḍ al-yahūd (Jewish Land). Gharian town had the smallest Jewish population of the three settlements. According to the 1944 census there were ninety Jews in Gharian, 343 in Tighrinn…
Keywords: Judaïsme -- Djebel Nefousa

The Names of the Jews of Lybia During the Italian Occupation : Gender, Society, and Culture - Henshke, Yehudit (La Rassegna mensile di Israel, 2017)
Keywords: Judaïsme -- Djebel Nefousa

Uccideteli tutti: Libia 1943: gli ebrei nel campo di concentramento fascista di Giado : una storia italiana - Salerno, Eric (Tascabili, 2012)
Keywords: Judaïsme -- Djebel Nefousa

Letters of medieval jewish traders - Goitein, S. D (Princeton University Press, 2016)
Keywords: Judaïsme -- Djebel Nefousa